Understanding smallholder decision‐making to increase farm tree diversity: Enablers and barriers for forest landscape restoration in Western Kenya - Bosshard, Ennia; Carter, Harrison; Aluso, Lillian Olimba; Chumba, Reuben; Kaiser-Bunbury, Christopher N.; Kettle, Chris J.; Nuno, Ana (Wiley, 2025)
Abstract Integrating diverse trees and shrubs (hereafter ‘trees’) in agricultural landscapes has emerged as a crucial nature‐based solution to the triple challenge of biodiversity loss, climate change and food security. The potential benefits of on‐farm trees for both people and nature, however, are often constrained by inadequate consideration of local socio‐ecological factors and an overall lack of species diversity. A deeper understanding of what drives farmers' decision‐making in diversifying farm trees is needed to ensure that scaling up tree‐based restoration efforts in smallholder landscapes delivers the promised benefits locally and globally. We conducted surveys with 620 smallholder farmers across Vihiga County in Western Kenya using an extended version of the Theory of Planned Behaviour to investigate potential drivers of smallholder intentions to grow more diverse woody plants on their farms. Data was analysed using Structural Equation Modelling (SEM). We found that farmers were more likely to diversify on‐farm trees if they had completed education beyond secondary school, derived all their income from their farms, were household heads and were among the wealthiest 20% of farmers. Our results revealed that farmers' decisions about increasing tree diversity were also influenced by socio‐psychological factors, namely their past experiences, the perceived behaviour and opinions of other farmers, their confidence in their ability to increase tree diversity, and their attitudes toward the expected outcomes of growing a wider range of tree species. Key barriers preventing farmers from diversifying were concerns about attracting harmful wildlife, decreasing soil fertility, small farm sizes, lack of time and knowledge, and certain cultural beliefs about planting trees. Synthesis and applications . Understanding the factors influencing farmers' intentions to increase tree diversity on their farms has substantial implications for the success of nature‐based solutions in Western Kenya and other densely populated smallholder landscapes. Addressing the identified barriers and enablers is crucial to design targeted interventions to promote sustainable tree diversification practices among smallholders to bolster local livelihoods and food security while contributing to biodiversity conservation and climate change mitigation. Read the free Plain Language Summary for this article on the Journal blog.